Assesment of serum alkaline phosphatase levels on the risk of presence hepatocelluler carcinoma in the liver transplantation patients (Annals of Medical Research, 2021)
Aim: Multivarious serum biomarkers have been investigated for their potential prognostic value in HCC. This aim of study evaluate the effects of Alkaline phosphatase levels on the risk of presence Hepathocelluler canser (HCC) among the liver transplantation patients.Material and Methods: Between 2004 and 2018 878 consecutive adult Liver Tranplantation patients in our center was reviewed These patients were divided into two groups according to presence of HCC [(n=208) HCC positive (Group A) and (n=670) HCC negative (Group B)].Data collection included, We evaluated the predictive values of liver fonctions tested liver enzymes (alanine aminotransferase [ALT], aspartate aminotransferase [AST], alkaline phosphatase [ALP], and gamma-glutamyltransferase [GGT], Hemoglobine (Hb), international normalized ratio (INR). The independent sample t test, Mann Whitney U test, chi-square test and Fisher exact test were used. to compare data. P-value of 0.05 was considered statistically significant.Results: A total 878 patients included in this study. 670 patients had HCC negative (Group A ) 208 had HCC positive(Grup B). The mean age in each group were 57.06 ± 11.27 years in group A and 50.46 ± 13.7 years in group B. (p=0.032). HOMA IR [5.2 (0.6-36) in group A, 4.2 (0.2-85.0) in group B] were lower in group B( p= 0.001). Serum ALP levels [ 184.39 ± 159.72 U/L in Group A, 159.7 2± 159.72 U/L in group B] were lower in group B (p = 0.046). Conclusion: Serum Alkaline phosphatase levels can be use as predictive component of the HCC. Follow-up studies are needed.
Keywords: Hepatocelluler carcinoma; alkaline phosphatase; liver transplantation